Renoprotective effects of remote ischemic preconditioning on acute kidney injury induced by repeated tourniquet application in patients undergoing extremity surgery - Ziying Tao; Ziying Tao; Yang Zhang; Erliang Kong; Haili Wei; Mingyue Li; Shuhui Sun; Liwei Liu; Liwei Liu; Daqing Yin; Xudong Feng (Frontiers in Medicine)
ObjectiveLimb ischemia–reperfusion injury caused by repeated tourniquet application usually leads to acute kidney injury, adversely affecting patient prognosis. This study aimed to investigate the renoprotective effect of remote ischemic preconditioning (RIPC) in patients undergoing extremity surgery with repeated tourniquet application.Methods64 patients were enrolled and randomly divided into an RIPC group and a control group, with 32 patients in each. Pretreatment was administered before surgery, and baseline characteristics were collected. Perioperative surgical characteristics, renal biomarkers, oxidative stress markers, inflammatory factors, and postoperative conditions were recorded.Results2 participant were excluded from each group, leaving 30 patients per group. There were no significant differences between the two groups regarding baseline characteristics and perioperative surgical characteristics (p > 0.05). Compared to the control group, the RIPC group showed a significant decrease in BUN and SCr at 48 h postoperatively (p < 0.05). Levels of Cys-C, [TIMP-2] × [IGFBP-7], KIM-1, IL-18, and NGAL were significantly reduced at the first and second tourniquet releases and at 24 h postoperatively in the RIPC group (p < 0.05). From the first tourniquet release to 48 h postoperatively, MDA levels were significantly lower (p < 0.05) and SOD levels were significantly higher (p < 0.05) in the RIPC group compared to the control group. Postoperative conditions did not differ significantly between the groups.ConclusionRIPC effectively mitigated acute kidney injury caused by repeated tourniquet application, offering a robust method for perioperative renal protection in patients undergoing extremity surgery. Future studies should explore the underlying mechanisms and long-term clinical outcomes of RIPC in broader patient populations.Clinical trial registrationhttps://www.chictr.org.cn/showproj.html?proj=231266.